2009
DOI: 10.1016/j.expneurol.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Flexor reflex decreases during sympathetic stimulation in chronic human spinal cord injury

Abstract: A better understanding of autonomic influence on motor reflex pathways in spinal cord injury is important to the clinical management of autonomic dysreflexia and spasticity in spinal cord injured patients. The purpose of this study was to examine the modulation of flexor reflex windup during episodes of induced sympathetic activity in chronic human spinal cord injury (SCI). We simultaneously measured peripheral vascular conductance and the windup of the flexor reflex in response to conditioning stimuli of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Although the exact mechanism through which spasticity pathophysiology is mediated by the ANS is unclear, a relationship is supported by previous studies. The stretch reflex in relaxed soleus muscle is enhanced by sympathetic outflow (Hjortskov et al, 2005), and a previous study demonstrated that, transiently depressed flexor reflex responses during periods of increased sympathetic reflex activity are induced by bladder percussion and noxious cutaneous stimulation in chronic spinal cord injured patients (Garrison & Schmit, 2009). Spinal interneurons common to the sympathetic and motor systems have been proposed to mediate the simultaneous modulations, and a neuro-anatomical study showed that a central somatomotor-sympathetic circuit is present at the brainstem level (Kerman, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Although the exact mechanism through which spasticity pathophysiology is mediated by the ANS is unclear, a relationship is supported by previous studies. The stretch reflex in relaxed soleus muscle is enhanced by sympathetic outflow (Hjortskov et al, 2005), and a previous study demonstrated that, transiently depressed flexor reflex responses during periods of increased sympathetic reflex activity are induced by bladder percussion and noxious cutaneous stimulation in chronic spinal cord injured patients (Garrison & Schmit, 2009). Spinal interneurons common to the sympathetic and motor systems have been proposed to mediate the simultaneous modulations, and a neuro-anatomical study showed that a central somatomotor-sympathetic circuit is present at the brainstem level (Kerman, 2008).…”
Section: Discussionmentioning
confidence: 97%